The camp-out mystery - Warner, Gertrude Chandler, 1890-1979.; Tang, Charles (Morton Grove, IL : A. Whitman, 1992)
While on a camping trip with their grandfather, the Alden children try to find out about the loud music and missing food that threatens to scare away other campers.
3.3
3-6
3-6
430
Keywords: Boxcar children (Fictitious characters) -- Fiction; Camping -- Fiction; Brothers and sisters -- Fiction; Grandfathers -- Fiction; Mystery and detective stories; Boxcar children (Fictional characters) -- Fiction; Camping -- Fiction; Siblings -- Fiction; Grandfathers -- Fiction; Mystery fiction